Aplikasi Sistem Informasi Perbaikan Ponsel di CV Anamely Semarang - Bahauddin, Ahmad; Somantri, Maman; Isnanto, R. Rizal (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
As a company that specializes in mobile phone telecommunication, CV Anamely Semarang has a service division that serves in maintenance and mobile phones repair. In performing its jobs, this division find problems in administration and management of data in order to obtain a receipt and the desired information in the form of data or reports. So far, the administration and management of data are still done manually. They make complicating in finding of data also the process of making reports and receipts. So that, it is required a computer system to solve those problems. Creating the application of this mobile phone repair information system uses UML for modelling systems. It is built using Delphi as programming language and MySQL as the database management system. As a result, this information system provides transaction processing services of mobile phones repair with their reports and printouts.Â Keyword :Â Â mobile phone repair, administration and management of data, models, Delphi, MySQL